2015
DOI: 10.18869/acadpub.aassjournal.3.3.57
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Backpack Weight on the Static and Dynamic Balances of Female Students

Abstract: The main aim of this study was to investigate the effects of carrying backpack on the balance of female students aged 9-11 years. In the present study, 30 students (mean age of 15.02±2.07 years, height of 140±8 cm, and weight of 41.51±15.26 kg and body mass index of 20.68±5.39 kg/m2) were randomly selected. Their static and dynamic balances were evaluated using single-leg stance and Y tests in both cases of with and without a backpack. Based on the research findings, there was a significant difference (P═0.035… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(26 reference statements)
0
0
1
Order By: Relevance
“…Besides, to improve posteromedial and posterolateral balance, the trunk and neck of the participant must flex more forward in addition to increased posterior shift of the center of body mass caused by backpack load. Bahiraei et al reported that backpack weight has the greatest effect on posteromedial direction and they also reported statistically different changes in anterior direction while the present study showed no differences in anterior direction (Bahiraei, Jafarian and Mohammad Ali Nasab, 2015). The discrepancy between the two studies in anterior direction may have been due to the age difference of the participants included in the studies.…”
Section: Resultscontrasting
confidence: 63%
“…Besides, to improve posteromedial and posterolateral balance, the trunk and neck of the participant must flex more forward in addition to increased posterior shift of the center of body mass caused by backpack load. Bahiraei et al reported that backpack weight has the greatest effect on posteromedial direction and they also reported statistically different changes in anterior direction while the present study showed no differences in anterior direction (Bahiraei, Jafarian and Mohammad Ali Nasab, 2015). The discrepancy between the two studies in anterior direction may have been due to the age difference of the participants included in the studies.…”
Section: Resultscontrasting
confidence: 63%